2003
DOI: 10.1128/jb.185.2.544-552.2003
|View full text |Cite
|
Sign up to set email alerts
|

Different Evolutionary Constraints on Chemotaxis Proteins CheW and CheY Revealed by Heterologous Expression Studies and Protein Sequence Analysis

Abstract: CheW and CheY are single-domain proteins from a signal transduction pathway that transmits information from transmembrane receptors to flagellar motors in bacterial chemotaxis. In various bacterial and archaeal species, the cheW and cheY genes are usually encoded within homologous chemotaxis operons. We examined evolutionary changes in these two proteins from distantly related proteobacterial species, Escherichia coli and Azospirillum brasilense. We analyzed the functions of divergent CheW and CheY proteins fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Thus, there is no strict length-class specificity between receptors and the CheA kinase under their control. Likewise, the CheW coupling protein has been shown to be exchangeable between distantly related bacterial species (Alexandre & Zhulin, 2003;Hamblin et al, 1997).…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…Thus, there is no strict length-class specificity between receptors and the CheA kinase under their control. Likewise, the CheW coupling protein has been shown to be exchangeable between distantly related bacterial species (Alexandre & Zhulin, 2003;Hamblin et al, 1997).…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…6). A gene encoding the response regulator CheY is usually included in a chemotaxis operon (2,90), but a cheY homolog was not found in the operon of D-4968. Two genes, LLB_2022 and LLB_2292 located outside the chemotaxis operon, encode CheY-like proteins, which may function together with the gene products of the chemotaxis operon.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the A. brasilense chemotaxis operon abolish taxis to all known stimuli and affect the pattern of motility (20), suggesting that this operon is the major regulator of motile behavior. It has also been shown that, despite their divergence in sequence, the chemotaxis proteins of A. brasilense are functional homologs of their E. coli counterparts (5).…”
mentioning
confidence: 99%